2019
DOI: 10.1038/s41598-019-44844-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in respiratory and circulatory cost during hypoxic walking: potential impact on oxygen saturation

Abstract: Energy expenditure (EE) during treadmill walking under normal conditions (normobaric normoxia, 21% O 2 ) and moderate hypoxia (13% O 2 ) was measured. Ten healthy young men and ten healthy young women walked on a level (0°) gradient a range of speeds (0.67–1.67 m s −1 ). During walking, there were no significant differences in reductions in arterial oxygen saturation (SpO 2 ) between the sexes. The hypoxia-induced incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…Appropriate energy prescription to maintain energy balance over time is dependent upon accurate calculation of RMR [3], so precise measurement of metabolism is of importance to researchers. For more than 20 years, researchers have controlled for menstrual cycle fluctuations when designing studies that require measurement of RMR in young women [4][5][6][7][8]. Measurements have typically been restricted to the follicular phase of the menstrual cycle, which requires young women to self-report the timing and onset of menstruation to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate energy prescription to maintain energy balance over time is dependent upon accurate calculation of RMR [3], so precise measurement of metabolism is of importance to researchers. For more than 20 years, researchers have controlled for menstrual cycle fluctuations when designing studies that require measurement of RMR in young women [4][5][6][7][8]. Measurements have typically been restricted to the follicular phase of the menstrual cycle, which requires young women to self-report the timing and onset of menstruation to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in SpO2 during exercise (exercise-induced arterial hypoxemia; EIAH) has been attributed to the ventilatory limits of the respiratory system. Horiuchi et al 's 68 findings that there are no sex-specific differences in SpO2 go against expectations that the smaller respiratory anatomy found in females and greater mechanical ventilatory constraints imposed on females predict more severe or frequent reductions in SpO2 (i.e. EIAH) in women than in men.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that although the endurance of both men and women during high altitude hypoxia will be significantly reduced, there were some differences in the underlying mechanism. In terms of cardiopulmonary function, it was found that the exercise-induced arterial hypoxemia at high altitude was more closely related to the heart rate in men than that in women, while ventilation and energy expenditure contributed more in women ( Horiuchi et al, 2019 ). In the aspect of oxygen transport and utilization, it was reported that although the hemoglobin content of women was lower than that of men, the affinity between oxygen and hemoglobin was weaker, which was conducive to the release of oxygen to tissue ( Balcerek et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%